2020
DOI: 10.1515/commun-2019-0123
|View full text |Cite
|
Sign up to set email alerts
|

Two-sided science: Communicating scientific uncertainty increases trust in scientists and donation intention by decreasing attribution of communicator bias

Abstract: AbstractPrevious research has shown that uncertainty communication by scientists (i. e., expressing reservations towards their own research) increases the public’s trust in their work. The reasons for this have not been elucidated, however. In the present study, we provide a theoretical explanation for this phenomenon. Specifically, we expected that attributed communicator bias would mediate the effect of uncertainty communication on trust. Results from a mixed-design experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 35 publications
0
14
1
Order By: Relevance
“…First, future studies should investigate whether recipients are also less likely to attribute communicator bias (Eagly et al, 1978) when sources communicate epistemic uncertainty. For example, Steijaert et al (2020) found that when a communicator discloses uncertainty recipients are less likely to ascribe communicator bias to the SI, leading to an increase in trust (compared to when no uncertainty is revealed). However, instead of applying single items, which has to be mentioned as a limitation of this study, it would be reasonable to develop a reliable scale to measure ascribed communicative motives.…”
Section: Discussionmentioning
confidence: 99%
“…First, future studies should investigate whether recipients are also less likely to attribute communicator bias (Eagly et al, 1978) when sources communicate epistemic uncertainty. For example, Steijaert et al (2020) found that when a communicator discloses uncertainty recipients are less likely to ascribe communicator bias to the SI, leading to an increase in trust (compared to when no uncertainty is revealed). However, instead of applying single items, which has to be mentioned as a limitation of this study, it would be reasonable to develop a reliable scale to measure ascribed communicative motives.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical evidence suggests that messages which label claims as based on “low-quality” research are rated as less trustworthy than those which reference “high-quality” research or make no mention of quality ( 26 , 27 ). Other studies have found that disclosure of evidence limitations by scientists in news or online reports can increase ( 28 , 29 ) or have no effect on perceptions of credibility or trustworthiness ( 30 , 31 ).…”
mentioning
confidence: 99%
“…We believe that this is the essential first step toward acceptance that published work is not "fact", even if published by scientists with strong reputations. This kind of appreciation of the presence of uncertainty in science is a key insight for calibrating public trust in science (Steijaert et al, 2020).…”
Section: Discussionmentioning
confidence: 99%